What can Schumpeter tell us about women entrepreneurship in Iran? - Sicard, Benoit (Journal of Entrepreneurship, Business and Economics, 2017)
Offering a view of entrepreneurship enhanced by innovation, Schumpeter underlined its importance in modern economics and business. The case of Iran, an economy recently opening to international markets and recovering from international sanctions, will be interesting when it comes to entrepreneurship. The aim of this paper is to reflect on women entrepreneurs in Iran using a Schumpeterian framework, in an attempt to come up with recommendations for the challenges they are facing. A review of contemporary research on entrepreneurship and innovation is conducted, taking into account their contributions to the initial theory built by Schumpeter. This is complemented with the Global Entrepreneurship Monitor (GEM) report for 2015-2016, as it provides comprehensive data on the target country (Iran) and topic (Entrepreneurship). It results that entrepreneurship in Iran demonstrates a relatively low inclination for innovation following the Schumpeterian thought, in which it is central along with other factors. A gap therefore exists between the approach taken and what Iranian new ventures feature. An enhanced entrepreneurial education is eventually identified as a way of fostering innovation to Iranian women entrepreneurs, a solution that could help overcome their issues. Thus, they would be able to take part more efficiently in entrepreneurial ventures, acting as a disruptive factor following Schumpeter’s view of innovation. A review of the literature about Schumpeter’s approach is conducted first, followed by a focus on women’s entrepreneurship in Iran. In addressing this issue, several recommendations providing ground for future research are suggested. Research paper Keywords: Iran, Entrepreneurship, Innovation, Education, Women Entrepreneurship Reference to this paper should be made as follows: Sicrad, B. (2017). “What can Schumpeter tell us about women entrepreneurship in Iran?”, Journal of Entrepreneurship, Business and Economics, Vol. 5, No. 1, pp. 185–215.